Detecting moisture transport pathways to the subtropical North Atlantic free troposphere using paired H 2 O- δ D in situ measurements - Schneider, Matthias; Dyroff, Christoph; Christner, Emanuel; García, Omaira Elena; Cuevas, Emilio; Bustos, Juan Jose; Ramos, Ramon; Guirado-Fuentes, Carmen; Barthlott, Sabine; Wiegele, Andreas; Sepúlveda, Eliezer; Gonzalez Ramos, Yenny; et al. (Atmospheric Chemistry and Physics, 2016)
We present two years of in situ measurements of water vapour (H[subscript 2]O) and its isotopologue ratio (δD, the standardized ratio between H[subscript 2][superscript 16]O and HD[superscript 16]O), made at two remote mountain sites on Tenerife in the subtropical North Atlantic. We show that the data – if measured during night-time – are well representative for the lower/middle free troposphere. We use the measured H[subscript 2]O-δD pairs, together with dust measurements and back trajectory modelling for analysing the moisture pathways to this region. We can identify four principally different transport pathways. The air mass transport from high altitudes and high latitudes shows two different scenarios. The first scenario brings dry air masses to the stations, as the result of condensation events occurring at low temperatures. The second scenario brings humid air masses to the stations, due to cross-isentropic mixing with lower-level and more humid air during transport since last condensation (LC). The third pathway is transportation from lower latitudes and lower altitudes, whereby we can identify rain re-evaporation as an occasional source of moisture. The fourth pathway is linked to the African continent, where during summer, dry convection processes over the Sahara very effectively inject humidity from the boundary layer to higher altitudes. This so-called Saharan Air Layer (SAL) is then advected westward over the Atlantic and contributes to moisten the free troposphere. We demonstrate that the different pathways leave distinct fingerprints on the measured H[subscript 2]O-δD pairs. European Commission. Framework Programme for Research and Innovation (FP7/2007-2013/ERC Grant agreement number 256961) Spain. Ministry of Economy and Competitiveness (project POLLINDUST (CGL2011-26259)) European Research Infrastructure for the observation of Aerosol, Clouds, and Trace gases (grant agreement number 262254) Spain. Ministry of Economy and Competitiveness (NOVIA project, CGL2012-37505)